Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015; Session “Epidemiology” - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2015)
Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015 ORGANIZING INSTITUTIONS European Society for Neonatology (ESN), European Society for Paediatric Research (ESPR), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI), with the local host of Hungarian Society of Perinatology and Obstetric Anesthesiology, Hungarian Society of Perinatology (MPT), supported by Council of International Neonatal Nurses (COINN), organizing secretariat MCA Scientific Events PROGRAMME COMMITTEE Artúr Beke (Hungarian Society), Morten Breindahl (ESN), Giuseppe Buonocore (UENPS), Pierre Gressens (ESPR), Silke Mader (EFCNI), Manuel Sánchez Luna (UENPS), Miklós Szabó (Hungarian Society of Perinatology), Luc Zimmermann (ESPR) Session “Epidemiology” ABS 1. A PERFORMANCE INDICATOR FOR THE PROLONGATION OF GESTATIONAL AGE • N. Lack ABS 2. LATE PRETERM NEONATES AND CAUSES OF ADMISSION TO THE NICU • S. Arayici, G. Kadioglu Simsek, B. Say, E. Alyamac Dizdar, N. Uras, F.E. Canpolat, S.S. Oguz ABS 3. INCIDENCE AND OUTCOMES OF METABOLIC DISORDERS IN VERY PRETERM INFANTS • O. Dobush, D. Dobryanskyy, Z. Salabay, O. Detsyk, O. Novikova, Y. Kuzminov ABS 4. MATERNAL FACTORS INFLUENCE INFANT’S VITAMIN D STATUS • H. Hauta-alus, E. Holmlund-Suila, M. Enlund-Cerullo, J. Rosendahl, S. Valkama, O. Helve, H-M. Surcel, O. Mäkitie, S. Andersson, H. Viljakainen ABS 5. THE HIGH PREVALENCE OF VITAMIN D DEFICIENCY IN A LARGE NUMBER OF PREGNANT WOMEN AND RELATED FACTORS IN ANKARA, TURKEY • G. Kadioglu Simsek, F. E. Canpolat, S. Arayici, G. Kanmaz Kutman, H.I. Yakut, Ö. Moraloğlu, B. Özkan ABS 6. SNAPPE-II: A VALUABLE PREDICTOR OF ADVERSE OUTCOMES IN PREMATURITY • P. Costa-Reis, R. Monteiro, M. Abrantes, P. Costa, A. Graça, C. Moniz ABS 7. THE ASSOCIATION BETWEEN MATERNAL AND FETAL 25OHD AND INFANT SIZE AND ADIPOSITY AT BIRTH, 6 MONTHS AND 2 YEARS OF AGE • M.K. Horan, J.M. Donnelly, C.A. McGowan, E.R. Gibney, F.M. McAuliffe ABS 8. IMPACT OF EX UTERO TRANSPORT, GENDER, AND ANTENATAL STEROIDS ON IN-HOSPITAL MORTALITY OF NEONATES IN HUNGARY: A RETROSPECTIVE COHORT STUDY • A. Jermendy, A. Valek, M. Szabo ABS 9. PREVALENCE OF VITAMIN D DEFICIENCY IN MOTHERS AND THEIR NEWBORNS IN A TUNISIAN TERTIARY CARE HOSPITAL • I. Ayadi, A. Ghdamssi, K. Bouzid, A. Bahlous, C. Amrouch, E. Ben Hamida, J. Abdelmoula , Z. Marrakchi ABS 10. PLACENTAL GROWTH FACTOR AND ENDOTHELIAL CELL-SPECIFIC MOLECULE 1 LEVELS IN DISCORDANT AND CONCORDANT TWINS AND THEIR RELATIONSHIP WITH FETAL GROWTH • G. Kadioglu Şimşek, S. Arayıcı, N. Okur, M. Büyüktiryaki, F.E. Canpolat, S.S. Oğuz ABS 11. THERMOREGULATION IN VERY LOW BIRTHWEIGHT INFANTS: A SURVEY OF CURRENT PRACTICE IN 87 NICUs • A. Perez, F. van der Meer, E. Vettorazzi, D. Singer ABS 12. REGIONAL ELECTRONIC RESEARCH SYSTEM E-WCZEŚNIAK (E-PREEMIE) IN MAZOVIA, POLAND • M.K. Borszewska-Kornacka ABS 13. MORTALITY AND EARLY MORBIDITY IN VERY LOW BIRTH WEIGHT NEWBORNS DURING THE TWELVE YEAR PERIOD IN SLOVAK REPUBLIC • M. Kovácsová, G. Magyarová, F. Bauer, R. Lelovská, K. Demová, E. Radvanská ABS 14. VLBW INFANTS OUTCOMES: A 12 YEARS REPORT IN A SOUTH AMERICAN NEONATAL NETWORK (NEOCOSUR) • I. D’Apremont, J.L. Tapia, G. Marshall, G. Musante, G. Mariani, J.M. Ceriani, A. Bancalari, J. Zegarra, P. Mena, C. Grandi, J. Fabres, J. Tavosnanska, J. Lacarruba for the Neocosur Neonatal Network ABS 15. IMPACT OF VARICELLA VACCINATION IN CHILDREN UNDER 1 YEAR OF AGE IN ITALY (2006-2011) • A.C. Di Pietro, A. Mattei, M. Sbarbati ABS 16. GENERAL HEALTH PERCEPTION OF YOUNG ADULTS BORN PRETERM OR WITH A VERY LOW BIRTH WEIGHT IN THE NETHERLANDS VERSUS PEERS • S.M. van der Pal, R.J.M. Perenboom, K.M. van der Pal-de Bruin ABS 17. INTRAUTERINE GROWTH RESTRICTION, HEAD SIZE AT BIRTH AND OUTCOME IN VERY PRETERM INFANTS • I. Guellec, S. Marret, O. Baud, G. Cambonie, A. Lapillonne, J.C. Roze, J. Fresson, C. Flamant, M.L. Charkaluk, C. Arnaud, P.Y. Ancel ABS 18. PREMEDICATION FOR NON-EMERGENCY NEONATAL INTUBATIONS: SURVEY OF PRACTICE ACROSS UNITED KINGDOM • V. Rajamoorthy, P. Dobbs, N. Agarwal, C.S. Narayanan, N. Merchant ABS 19. HEALTH-RELATED QUALITY OF LIFE IN VERY PRETERM CHILDREN ASSESSED AT SCHOOL AGE: COMPARISON BETWEEN THE CHILDREN’S AND PARENTS’ REPORTS • M. Cuttini, I. Croci, L. Herich, M. Carrozzi, V. Chiandotto, S. Vicari, M. Raponi ABS 20. THE EPIDEMIOLOGY OF LISTERIOSIS DURING PREGNANCY IN NORTHERN ITALY • E. Amato, M. Gori, P. Huedo, M. Pontello ABS 21. HEARING IMPAIRMENT IN PREMATURE NEWBORNS – ANALYSIS BASED ON THE NATIONAL HEARING SCREENING DATABASE • K. Wroblewska-Seniuk, P. Dabrowski, G. Greczka, J. Mazela ABS 22. IS ROUTINE USE OF ANTIBIOTICS IN PRETERM INFANTS BORN BY ELECTIVE CAESAREAN SECTION (COLD SECTION) WITH RESPIRATORY DISTRESS SYNDROME JUSTIFIABLE? • R. Onita, H. Gowda ABS 23. CLEARING SERIOUS INFECTION: A QUALITY IMPROVEMENT INITIATIVE TO REDUCE NOSOCOMIAL INFECTION • C. Duncan, C. Mayes, J.S. Craig ABS 24. VAGINAL UREAPLASMA PARVUM BUT NOT UREALYTICUM COLONIZATION AT 12 TO 14 WEEKS OF GESTATION IS SIGNIFICANTLY ASSOCIATED WITH PRETERM DELIVERY • J. Rittenschober-Boehm, D. Kasper, S. Schulz, B. Pimpel, T. Waldhoer, E. Hafner, G. Sliutz, A. Witt, A. Berger ABS 25. RESPIRATORY OUTCOMES IN LATE AND MODERATELY PRETERM INFANTS: RESULTS FROM A POPULATION-BASED STUDY • S. Robinson, S.E. Seaton, R.J. Matthews, S. Johnson, E.S. Draper, B.N. Manktelow, L.K. Smith, N. Marlow, D.J. Field, E.M. Boyle ABS 26. PERFLUOROALKYL ACID EXPOSURE AND INFANTILE COLIC: A STUDY IN THE DANISH NATIONAL BIRTH COHORT • C.C. Bach, I. Milidou, B.H. Bech, E.A. Nohr, C. Søndergaard, J. Olsen, T.B. Henriksen ABS 27. NORMAL REFERENCE VALUES FOR UMBILICAL CORD ARTERIAL PH IN PRETERM AND TERM INFANTS • B. Skiöld, O. Stephansson, S. Johansson ABS 28. PREDICTORS OF HOSPITAL DISCHARGE IN A SWISS NATIONAL COHORT OF VERY PRETERM INFANTS • C. Rüegger, M. Adams, S. Schulzke, S. Wellmann; Swiss Neonatal Network ABS 29. HYPOTHERMIA AND RESPIRATORY DISTRESS SYNDROME IN PREMATURE INFANTS • C.F. Jensen, F. Ebbesen, J.P. Petersen, A.S. Sørensen, C.C. Bach, T.B. Henriksen ABS 30. INCIDENCE OF ACUTE KIDNEY INJURY IN PREMATURE INFANTS ACCORDING TO ACUTE KIDNEY INJURY NETWORK (AKIN) CRITERIA • F.S. Cardona, T.M. Ehringer, S. Dufek, L. Unterasinger, D. Csaicsich, C. Aufricht ABS 31. EARLY LIFE EXPOSURE TO ENDOCRINE DISRUPTORS AND TSH LEVELS IN NEWBORNS – ANALYSIS OF THREE EUROPEAN COHORTS • M. de Cock, M.R. de Boer, E. Govarts, G. Schoeters, L. Palkovicova, T. Trnovec, N. Iszatt, M. Eggesbo, J. Legler, M. van de Bor ABS 32. RELATIVE SIZE AT BIRTH AND PARENTAL CARDIOVASCULAR MORBIDITY, A NATIONAL REGISTER STUDY • P. Hovi, S. Alenius, S.P.K. Näsänen-Gilmore, M. Vääräsmäki, M. Gissler, E. Kajantie ABS 33. GILBERT GENOTYPES AND RESPIRATORY DISEASE IN VERY PRETERM INFANTS, A COHORT STUDY • F. Ebbesen, M.V. Hollegaard, S. Andersson, D.M. Hougaard, O. Thorlacius-Ussing, T.B. Henriksen